Multiple Layers of Regulation on Leaf Senescence: New Advances and Perspectives - Zhang, Yue-Mei; Guo, Pengru; Xia, Xinli; Guo, Hongwei; Li, Zhonghai (Frontiers in Plant Science, 2021)
Leaf senescence is the last stage of leaf development and is an orderly biological process accompanied by degradation of macromolecules and nutrient recycling, which contributes to plant fitness. Forward genetic mutant screening and reverse genetic studies of senescence-associated genes (SAGs) have revealed that leaf senescence is a genetically regulated process, and the initiation and progression of leaf senescence are influenced by an array of internal and external factors. Recently, multi-omics techniques have revealed that leaf senescence is subjected to multiple layers of regulation, including chromatin, transcriptional and post-transcriptional, as well as translational and post-translational levels. Although impressive progress has been made in plant senescence research, especially the identification and functional analysis of a large number of SAGs in crop plants, we still have not unraveled the mystery of plant senescence, and there are some urgent scientific questions in this field, such as when plant senescence is initiated and how senescence signals are transmitted. This paper reviews recent advances in the multiple layers of regulation on leaf senescence, especially in post-transcriptional regulation such as alternative splicing.